Effect of ecotourism on plant biodiversity in Chelmir zone of Tandoureh National Park, Khorasan Razavi Province, Iran - AMIRHOSSEIN ZARGHI; SEYED MOHSEN HOSSEINI (Society for Indonesian Biodiversity, 2014)
Zarghi A, Hosseini SM. 2014. Effect of ecotourism on plant biodiversity in Chelmir zone of Tandoureh National Park, Khorasan Razavi Province, Iran. Biodiversitas 15: 224-228. Tourism in protected areas is generally viewed as a primary source of promoting economicand social growth to local communities and commonly perceived to safeguard biodiversity. However, in the last few decades anincreasing number of visitors along with more diverse activities are having greater impacts on nature. Hence due to importance ofecotourism in Iran, the effect of ecotourism on plant biodiversity in Chelmir zone was investigated. To acquire the aim of the article, thesampling area was selected under the condition that the ecotourism is solely the variable factor and the slope, direction and height areconsidered constant factor after evaluation of the ecological land unit drawings. Two zones of high pressured and low pressuredecotourism were considered after evaluation of related drawings. Samples were taken in spring 2010. For evaluation of the plantbiodiversity 60 samples of 1m2 (30 samples in each zone) were taken randomly and then the list of flora and the cover percentage ofvegetation were recorded and then the percentage of vegetation data were analyzed in Biopast software and the biodiversity (Shanon,Simpson) richness (Menhinick, Margalef) evenness (Dominance, Berger-Parker) and dominance (Evenness, Equitability) indices werecalculated. The mentioned indices were inserted in SPSS II software and the data normality was tested through Kolomogrov-Smirnovtest. Due to data normality, non-paired T test was used in order to compare diversity analysis. The results indicate that the diversity,richness, dominance and evenness indices show significant effects of ecotourism on biodiversity indices.